Antifungal Interventions and Clinical Outcomes: A Review - Simran, Simran; Габа, Пунам; Схарма, Неелам; Синг, ОМИЉЕНО (Scripta Medica, 2026)
Fungal infections pose a significant risk to public health since they are linked to high rates of illness and death, particularly in immunocompromised individuals. Therapy is difficult because there are few antifungal drugs available and many of them are harmful. Fungi have also evolved defence mechanisms to fight these drugs. This article overlooks at antifungal drugs that are currently on the market, discusses resistance mechanisms and investigates new treatment-enhancing strategies. Combinations of antifungal drugs can increase effectiveness and reduce toxicity. New drug formulations, including nanoparticles are being studied to improve dispersion and reduce adverse effects. Furthermore, commercially marketed prescriptions may become more effective if their chemical makeup is changed. Additionally, novel drugs are being tested more rapidly and precisely using mini-host animal models. These creative methods could expedite the process and enhance patient outcomes. This study notes multiple challenges, such as patient peculiarities, intricate drug interactions and pathogen diversity, while also emphasising the advancements in antifungal therapy. Enhancing efficacy and reducing toxicity requires advancements in diagnosis, treatment and medicine. More studies on emerging fungal infections and antibiotic resistance are needed.